The constitution of the Socialist Federal Republic of Yugoslavia. Constitutional amendments. [Ed.: D. Durović. Transl. by M. Pavičić] ([Secretariat of the Federal Assembly Information Service], 1969)
Original title: Ustav Socijalističke Federativne Republike Jugoslavije.